2021
DOI: 10.1016/j.heliyon.2021.e06581
|View full text |Cite
|
Sign up to set email alerts
|

The real value of words: how target language linguistic modelling of foreign language teaching content shapes students’ professional identity

Abstract: The paper focuses on the methods of linguistic analysis in the sphere of teaching foreign languages as a form of shaping students' identity. By putting forward the hypothesis that proper language acquisition should be based on fundamental cultural values and their adequate linguistic interpretation, we propose the pragmatic and axiological linguistic modelling as an indispensable FLT tool, develop its methodology and prove its future validity on the material of FLT discourse. The research gives a step-by-step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…This prophetic education value is a pillar of positive politeness because it is advantageous and inspires others ( Baldacchino, 2018 ). Therefore, harmoniously choosing and developing teaching materials signifies the prophetic education on children’s politeness ( Fatma et al., 2019 ; Hadi, 2015 ; Prayitno, 2010 ; Bagiyan et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…This prophetic education value is a pillar of positive politeness because it is advantageous and inspires others ( Baldacchino, 2018 ). Therefore, harmoniously choosing and developing teaching materials signifies the prophetic education on children’s politeness ( Fatma et al., 2019 ; Hadi, 2015 ; Prayitno, 2010 ; Bagiyan et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is owing to the fact that one's professional identity is established by the creation and updating of one's professional language. Additionally, Bagiyan et al, (2021) found that professional identification was established through future specialist's professional preparation, and was indistinguishably linked to the acquisition of required professional competencies. In the same way as any professional understanding is conveyed by texts that shape a professional image of the world, as well as standards and models of behaviour, any professional knowledge is represented by texts.…”
Section: Students' Needmentioning
confidence: 99%
“…Иными словами, манипулирование сознанием адресата, в первую очередь, реализуется через убеждение абитуриента в важности формирования или трансформации его собственной идентичности, будь то личностный или же профессиональный аспект, см. : [Bagiyan et al, 2021]. Данное наблюдение, конечно, требует более глубокой проработки и анализа в последующих лингвоаксиологических исследованиях.…”
Section: сводный прагма-аксиологический и психолингвистический анализ рекламного университетского дискурсаunclassified